STUDI POTENSI PEMBANGKIT LISTRIK TENAGA PIKO HIDRO DI ALIRAN SUNGAI IRIGASI SUBAK WERDI PUTRA SEDANA KABUPATEN BADUNG - Wira Negara, Ida Bagus Gede; Janardana, I Gusti Ngurah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
In addition to solar and wind energy, the hydrological cycle can be used for energy sources by utilizing waves or currents or water potential e nergy due to differences in water level. This water energy is energy that has not been utilized optimally. In general, the utilization of this energy source is carried out on a large scale and requires very large costs. According to observations, the Dukuh Moncos Traditional Village has the potential for generating electricity because the river flows are quite stable and sustainable. In this study, a study was conducted on the potential of the Werdi Putra Sedana irrigation river flow around the Kelaci Templ e, Dukuh Moncos Traditional Village, Sobangan Village, Mengwi District, Badung Regency to be utilized as a pico hydro power plant with quantitative and descriptive methods. This study was carried out by measuring the water flow rate then measuring the head or height difference then continuously measuring the hydraulic potential, from the measurement stage and obtaining the results then calculating the potential power generated by the irrigation river so that the power generated was obtained. The flow of the Werdi Putra Sedana subak river in Banjar Hamlet Moncos, Sobangan Village, Mengwi District, Badung Regency has the potential to be used as an alternative energy source, namely a pico hydro power plant (PLTPH) with an average power of 3.86 kW.